Copper alloys having high strength and high conductivity and methods for making such copper alloys
Patent Information
- Application Number
- JP2021560246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-12
- Filing Date
- 2020-04-09
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-04-09
AI Technical Summary
【0017】以下は、本明細書で開示される例示的な実施形態を制限する目的ではなく、例示する目的で提示される、図の簡単な説明である。
Smart Images

Figure 0007644022000012 
Figure 0007644022000013 
Figure 0007644022000001
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. Provisional Patent Application No. 62 / 833,012, filed April 12, 2019, which is incorporated by reference in its entirety herein.
[0002]
[0002] This disclosure relates to copper alloys having a combination of high 0.2% offset yield strength and high electrical conductivity. Also disclosed are methods of making such copper alloys, electrical and other components that employ the copper alloys, and components and articles made from such copper alloys. [Background technology]
[0003]
[0003] Heat treatable copper alloys can be produced using existing methods to provide high electrical conductivity. However, these heat treatable copper alloys are often not selected for use in commercial electronic devices, components, and parts. This is in part because the copper alloys, even after full age hardening, do not exhibit a high enough strength-to-weight ratio to replace other choices such as aluminum or copper alloys, especially in high current applications. Summary of the Invention [Problem to be solved by the invention]
[0004] It would be desirable to provide high electrical conductivity copper alloys with improved thermomechanical properties, as well as methods for maximizing strength-to-weight ratio, formability, electrical current carrying capability, and / or thermal conductivity. [Means for solving the problem]
[0005]
[0005] The present disclosure relates to copper alloys having a 0.2% offset yield strength of at least 70 ksi and an electrical conductivity of at least 75% IACS. Also disclosed herein are methods that can be applied to copper alloys to increase their 0.2% offset yield strength and / or their ultimate tensile strength.
[0006] In various embodiments, a copper alloy is disclosed that includes about 0.5 wt% to about 1 wt% chromium, about 0.02 wt% to about 0.1 wt% silicon, about 0.1 wt% to about 0.2 wt% silver, about 0.015 wt% to about 0.05 wt% titanium, about 0.02 wt% to about 0.06 wt% zirconium, and the balance copper. The copper alloy has a 0.2% offset yield strength of at least 75 ksi and an electrical conductivity of at least 75% IACS.
[0007]
[0007] The copper alloy may have an ultimate tensile strength of at least 80 ksi. The copper alloy may have a total elongation at break of at least 7%. The copper alloy may have a formability ratio of 0.0 / 0.0, or better than 1.0 / 1.0. Combinations of any two or more of these properties are also contemplated.
[0008] In some embodiments, the copper alloy has a 0.2% offset yield strength of at least 75 ksi and an electrical conductivity of at least 80% IACS. In other embodiments, the copper alloy has a 0.2% offset yield strength of at least 75 ksi, an electrical conductivity of at least 75% IACS, an ultimate tensile strength of at least 80 ksi, and a total elongation to break % of at least 8%.
[0009] In certain embodiments, the copper alloy may be free of tin or beryllium.
[0010] Also disclosed herein are articles formed from the copper alloys discussed above and further herein.
[0010]
[0011] Also disclosed is a method for making the Cu-Cr-Si-Ag-Ti-Zr alloy having the aforementioned 0.2% offset yield strength and electrical conductivity. An initial copper alloy is cold worked to a first cold work percentage (CW%). The cold worked copper alloy is then solution annealed a first time for a first period of time. The annealed copper alloy is cold worked a second time to a second CW%. The cold worked copper alloy is solution annealed a second time for a second period of time. The solution annealed copper alloy is then cold worked a third time to a third CW%. The cold worked copper alloy is then aged for a third period of time to obtain a copper alloy having improved strength and electrical conductivity.
[0011]
[0012] The first CW% can be about 80% to about 95%. The second CW% can be about 30% to about 80%. The third CW% can be about 40% to about 80%. The minimum cumulative cold working from all three cold working steps should be at least 85%.
[0012]
[0013] The first solution anneal may be carried out at a temperature of about 950° C. to about 1050° C. The first time period may be from about 1 minute to about 10 minutes, including from about 2.5 minutes to about 5 minutes.
[0014] The second solution annealing can be carried out at a temperature of about 950° C. to about 1050° C. The second time period can be from about 1 minute to about 10 minutes, including from about 1.3 minutes to about 4 minutes.
[0013]
[0015] The aging treatment may be carried out at a temperature of about 400° C. to about 500° C. The third period of time may be about 4 hours to about 14 hours. The aging treatment may be carried out in a full hydrogen atmosphere.
[0016] These and other non-limiting features of the present disclosure are more particularly discussed below.
[0014]
[0017] The following is a brief description of the figures, which are presented for purposes of illustration, but not for purposes of limitation, of the exemplary embodiments disclosed herein. [Brief description of the drawings]
[0015] [Figure 1]
[0018] 1 is a flow diagram illustrating a method for preparing a high yield strength, high conductivity Cu—Cr—Si—Ag—Ti—Zr alloy according to one embodiment of the present disclosure. [Diagram 2]
[0019] 1 is an image of an etched high conductivity copper alloy according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016]
[0020] A more complete understanding of the components, methods and apparatus disclosed herein can be obtained by reference to the accompanying figures, which are schematic diagrams merely for convenience and ease of demonstrating the present disclosure, and thus are not intended to illustrate the relative sizes and dimensions of the devices or their parts and / or to define or limit the scope of the example embodiments.
[0017]
[0021] The singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.
[0022] As used in the specification and claims, the terms "comprise," "include," "having," "has," "can," "contain," and variations thereof, are intended as open-ended transitional phrases, terms, or phrases that require the presence of the named ingredients / steps and permit the presence of other ingredients / steps. However, such descriptions also describe compositions or methods as "consisting of" and "consisting essentially of" the recited ingredients / steps, thereby allowing for only the named ingredients / steps to be present along with any unavoidable impurities that may result therefrom, and should be interpreted to exclude other ingredients / steps.
[0018]
[0023] Numerical values in the specification and claims of this application should be understood to include numerical values that are the same when converted to the same number of significant digits, and numerical values that differ from the stated value by less than experimental error of conventional measurement techniques of the type described in this application to determine the value.
[0019]
[0024] All ranges disclosed herein are inclusive of the recited endpoints and are independently combinable (e.g., the range "2 grams to 10 grams" includes its endpoints 2 grams and 10 grams, and all intermediate values).
[0020]
[0025] A value modified by one or more terms such as "about" and "substantially" may not be limited to the exact value specified. Approximate terms may correspond to the precision of an instrument for measuring the value. The modifier "about" should also be considered as disclosing a range defined by the absolute values of the two endpoints. For example, the expression "about 2 to about 4" also discloses the range "2 to 4". The term "about" can refer to ±10% of the indicated number.
[0021]
[0026] This disclosure may refer to temperatures for certain method steps. Note that these generally refer to the temperature at which a heat source (e.g., a furnace) is set, and do not necessarily refer to the temperature that must be obtained by a material exposed to the heat.
[0022]
[0027] Disclosed herein is a copper alloy comprising copper further alloyed with chromium, silicon, silver, titanium and zirconium. The copper alloy does not contain beryllium or tin. The disclosed alloy is suitable for strengthening without substantial loss of electrical conductivity using tempering operations, such as annealing, cold working (e.g., cold rolling with or without tension, aging effect, and various combinations thereof). The disclosed copper alloy exhibits both high 0.2% offset yield strength and high electrical conductivity with appropriate tempering.
[0023]
[0028] According to another aspect of the present disclosure, methods of producing such copper alloys that exploit multiple strengthening mechanisms are disclosed. More specifically, the disclosed methods include extensively cold working copper alloys and solution annealing them to build a cold worked single phase dislocation structure. The alloys are then aged to build a very high density of small to medium sized precipitates. These methods can be applied to copper alloys, thereby making them precipitation strengthened.
[0024]
[0029] The copper alloy of the present disclosure contains chromium, silicon, silver, titanium, zirconium, and balance copper. Chromium is present in the copper alloy in an amount of about 0.5 wt% to about 1 wt%, including about 0.55 wt% to about 0.85 wt% or about 0.65 wt% to about 0.80 wt%. Silicon is present in the copper alloy in an amount of about 0.02 wt% to about 0.1 wt%, including about 0.03 wt% to about 0.08 wt% or about 0.04 wt% to about 0.065 wt%. Silver is present in the copper alloy in an amount of about 0.1 wt% to about 0.2 wt%, including about 0.11 wt% to about 0.15 wt% or about 0.11 wt% to about 0.14 wt%. Titanium is present in the copper alloy in an amount of about 0.015 wt% to about 0.05 wt%, including about 0.02 wt% to about 0.04 wt%. Zirconium is present in the copper alloy in an amount of about 0.02 wt% to about 0.06 wt% or up to 0.05 wt%, including about 0.02 wt% to about 0.04 wt%. The balance of the copper alloy, excluding impurities, is copper. In other words, copper may be present in an amount of about 98.59 wt% to about 99.345 wt%, or at least 98.8 wt%. Any combination of these amounts of each element is contemplated.
[0025]
[0030] In certain embodiments, the copper alloy may include about 0.55 wt% to about 0.85 wt% chromium, about 0.03 wt% to about 0.08 wt% silicon, about 0.11 wt% to about 0.15 wt% silver, about 0.015 wt% to about 0.05 wt% titanium, about 0.02 wt% to about 0.04 wt% zirconium, and the balance copper.
[0026]
[0031] In a particular embodiment, the copper alloy may include about 0.66 wt% chromium, about 0.04 wt% silicon, about 0.11 wt% silver, about 0.02 wt% titanium, about 0.03 wt% zirconium, and the balance copper.
[0027]
[0032] In other specific embodiments, the copper alloy may include about 0.65 wt% to about 0.80 wt% chromium, about 0.04 wt% to about 0.065 wt% silicon, about 0.11 wt% to about 0.14 wt% silver, about 0.02 wt% to about 0.04 wt% titanium, about 0.02 wt% to about 0.04 wt% zirconium, and the balance copper.
[0028]
[0033] Copper alloys may also have some impurities, but desirably do not. Examples of such impurities include tin, beryllium, titanium, magnesium, boron, oxygen, nickel, iron, cobalt, and sulfur. Some of these elements may be added during processing for specific purposes. For example, boron and iron can be used to further enhance the formation of equiaxed grains during solution heat treatment. In the manufacturing method of the present disclosure, these elements are ideally not used. For the purposes of this disclosure, any of these elements in an amount less than 0.01 wt% should be considered an unavoidable impurity, i.e., their presence is neither intended nor desired, and the total amount of such unavoidable impurities is typically less than 0.05 wt%. Some embodiments may further include iron and cobalt, but desirably do not. Some embodiments may contain up to 0.05 wt% iron and / or cobalt. However, preferred embodiments meet the performance and property characteristics as disclosed herein in the absence of these two elements.
[0029]
[0034] It is noted that zirconium is intentionally added to act as a deoxidizer and should not be considered an impurity. Zirconium silicides may affect yield strength and are desirably not present in the copper alloys of the present disclosure. The copper alloys of the present disclosure should be substantially devoid of such zirconium silicides. Preferably, zirconium is present in the form of zirconium oxide. Desirably, such oxides are in the form of small particles and are not present as continuous stringers.
[0030]
[0035] After processing, the Cu-Cr-Si-Ag-Ti-Zr alloy will have certain properties. The final copper alloy may have a 0.2% offset yield strength of at least 70 ksi, or at least 72 ksi, or at least 75 ksi, and / or up to 90 ksi. The final copper alloy may have an ultimate tensile strength of at least 70 ksi, or at least 75 ksi, or at least 80 ksi, and / or up to 90 ksi. The final copper alloy may have a modulus of elasticity of at least 20 million psi (Msi), or at least 21 Msi, and / or up to 25 Msi. The final copper alloy may have a formability ratio of at least 1.0 / 1.0 and may have a 0.0 / 0.0 R / t ratio. The final copper alloy may have a total elongation to break % of at least 7%, or at least 7.5%, or at least 8%, or at least 9%, and / or up to 12%. The final copper alloy may have an electrical conductivity of at least 50% IACS, or at least 60% IACS, or at least 70% IACS, or at least 71% IACS, or at least 72% IACS, or at least 73% IACS, or at least 74% IACS, or at least 75% IACS, or at least 76% IACS, or at least 77% IACS, or at least 78% IACS, or at least 79% IACS, or at least 80% IACS, and / or up to 85% or up to 90% IACS.
[0031]
[0036] Any combination of 0.2% offset yield strength, ultimate tensile strength, formability ratio, total elongation to break, and electrical conductivity discussed above is contemplated for the Cu-Cr-Si-Ag-Ti-Zr alloys of the present disclosure.
[0032]
[0037] In certain embodiments, the Cu-Cr-Si-Ag-Ti-Zr alloys of the present disclosure have a 0.2% offset yield strength of at least 70 ksi and an electrical conductivity of at least 75% IACS.
[0033]
[0038] In certain embodiments, the Cu-Cr-Si-Ag-Ti-Zr alloys of the present disclosure have a 0.2% offset yield strength of at least 75 ksi and an electrical conductivity of at least 80% IACS.
[0034]
[0039] In certain embodiments, the Cu-Cr-Si-Ag-Ti-Zr alloys of the present disclosure have a 0.2% offset yield strength of at least 70 ksi, an electrical conductivity of at least 75% IACS, an ultimate tensile strength of at least 75 ksi, and a % total elongation to fracture of at least 7%.
[0035]
[0040] Zirconium in Cu-Cr-Si-Ag-Ti-Zr alloys is used as a deoxidizer because it does not melt at low temperatures, does not generally have a detrimental effect on electrical conductivity in the final alloy, does not tend to stay in solution with the copper, and usually improves yield strength. In comparison, magnesium burns off quickly and can cause the melt to "spit", and it can melt at low temperatures, thereby causing difficulties during hot rolling. Manganese does not burn off quickly enough and can have a detrimental effect on electrical conductivity. Cadmium can cause problems during hot rolling and is also toxic. Lithium is relatively expensive.
[0036]
[0041] 1 , a method 100 for making a Cu-Cr-Si-Ag-Ti-Zr alloy is illustrated in accordance with one embodiment of the present disclosure. The method 100 begins at step 110, where a copper alloy is provided. This Cu-Cr-Si-Ag-Ti-Zr alloy, also referred to as an initial copper alloy, has initial properties, such as, for example, an initial 0.2% offset yield strength, an initial ultimate tensile strength, an initial formability ratio, an initial total elongation to failure %, and / or an initial electrical conductivity (i.e., IACS %), prior to any processing according to the present disclosure.
[0037]
[0042] The initial copper alloy may be provided in the form of a casting. Alternatively, the initial copper alloy may be subjected to one or more further pre-processing steps, including, for example, casting, cropping, milling, hot rolling, flat milling, to obtain a desired shape. These pre-processing steps generally do not change the properties of the copper alloy.
[0038]
[0043] In a first step 120, the initial copper alloy is cold worked a first time to a first cold work percentage (CW%). Cold working is a metal forming process, typically performed at about room temperature, in which the alloy is passed between rolls, forced into a die, or otherwise cold worked to reduce the cross section of the alloy and make the cross sectional dimensions uniform. This increases the strength of the alloy. The degree of cold working performed is indicated in terms of percent thickness reduction or percent area reduction, and is referred to in this disclosure as cold work percentage (CW%). In certain embodiments, the initial copper alloy is cold worked to a first CW% of about 60 CW% to about 95 CW%, including about 80 CW% to about 95 CW% and about 82 CW% to about 92 CW%.
[0039]
[0044] In the second step 130, the cold worked copper alloy is solution annealed a first time. More specifically, the copper alloy cold worked to a first CW% is solution annealed. Solution annealing involves heating the precipitation hardenable alloy to a temperature high enough to convert the microstructure to a single phase. Rapid quenching to room temperature places the alloy in a supersaturated state which makes the alloy soft and ductile, aids in grain size control, and prepares the alloy for aging. Subsequent heating of the supersaturated solid solution allows precipitation of strengthening phases and hardens the alloy. After any solution annealing, a water quench should be performed to "lock in" the result. The quench rate should be a minimum of -1.1°C (30°F) / sec, with quench rates of up to 37.8°C (100°F) / sec being acceptable.
[0040]
[0045] The first solution anneal of step 130 may be performed at a temperature of about 950° C. (1742° F.) to about 1050° C. (1922° F.) or about 980° C. (1796° F.) to about 1000° C. (1832° F.). The first solution anneal may be performed for a first period of time of about 1 minute to about 10 minutes, and in a more specific embodiment, about 2.5 minutes to about 5 minutes.
[0041]
[0046] In step 140, the solution annealed copper alloy is cold worked a second time to a second cold work percentage (CW%). In certain embodiments, the second CW% is between about 30 CW% and about 80 CW%.
[0042]
[0047] In step 150, the copper alloy is solution annealed a second time. The second solution anneal in step 150 may be performed at a temperature of from about 950° C. (1742° F.) to about 1050° C. (1922° F.) or from about 980° C. (1796° F.) to about 1000° C. (1832° F.). The second solution anneal may be performed for a second time period of from about 1 minute to about 10 minutes, including from about 1.3 minutes to about 4 minutes.
[0043]
[0048] In step 160, the copper alloy is cold worked a third time to a third cold work percentage (CW%). In certain embodiments, the third CW% is between about 30 CW% and about 80 CW%, including between about 40 CW% and about 80 CW%. The minimum cumulative cold work for all three cold working steps is at least 85 CW%.
[0044]
[0049] It is noted that in some situations where the initial copper alloy casting is particularly thick, a third solution anneal and a fourth cold work may be desired. In such cases, the third solution anneal may be performed according to the parameters described for step 150, and the fourth cold work may be performed according to the parameters described for step 160.
[0045]
[0050] Next, in step 170, the cold worked copper alloy is aged for a third period of time to obtain a copper alloy having an improved 0.2% offset yield strength. Aging is a heat treatment technique that creates impurity phases of order and fine grains (i.e., precipitates) that impede defect migration in the crystal lattice. This hardens the alloy. In certain embodiments, the alloy is aged at a temperature of about 400°C (752°F) to about 500°C (932°F) or about 420°C (788°F) to about 450°C (842°F). The aging may be performed for a third period of about 4 hours to about 20 hours, or about 4 hours to about 8 hours, or about 6 hours to about 18 hours. It is noted that the aging may be performed at multiple different temperatures in these temperature ranges, with the total aging time being considered as the third period of time. Typically, when multiple different temperatures are used for aging, each subsequent aging temperature is lower than the previous aging temperature.
[0046]
[0051] Copper alloys may be aged in a full hydrogen atmosphere. The term "full" means that the atmosphere in which aging takes place is 100% hydrogen (H2). For comparison, dry air contains approximately 0.5-1 ppmv of hydrogen (H2). Aging in a full hydrogen atmosphere makes sense because the thermal conductivity of hydrogen exceeds that of air.
[0047]
[0052] After steps 120-170, the copper alloy may undergo one or more post-processing steps 180. For example, the copper alloy may be pickled and / or brushed. The method ends in step 190.
[0048]
[0053] The resulting copper alloy after step 170 has an improved 0.2% offset yield strength and can be considered the "final" copper alloy. The final Cu-Cr-Si-Ag-Ti-Zr alloy can have one or more final properties, such as final 0.2% offset yield strength, final ultimate tensile strength, final formability ratio, final total elongation to failure %, and final electrical conductivity (i.e., IACS %), as previously described.
[0049]
[0054] 0.2% offset yield strength, ultimate tensile strength, and % total elongation at break are measured according to ASTM E8. Elastic modulus is measured according to ASTM E111-17. Formability can be measured by the formability ratio or R / t ratio (i.e., flexural strength). This specifies the minimum inside radius of curvature (R) required to bend a strip of thickness (t) 90° without failure, i.e., the formability ratio is equal to R / t. Materials with good formability have low formability ratios (i.e., low R / t), in other words, the lower the R / t, the better. Formability ratios can be measured using a 90° V-block test, where a punch with a given radius of curvature is used to force a test strip into a 90° die, and then the outside diameter of the bend is inspected for cracks. Formability ratios can also be reported as the ratio of longitudinal (good way) formability to transverse (bad way) formability, or GW / BW.
[0050]
[0055] According to a third aspect of the present disclosure, articles formed from these Cu-Cr-Si-Ag-Ti-Zr copper alloys are described. The copper alloys of the present disclosure have a combination of good 0.2% offset yield strength, high formability, and high electrical conductivity.
[0051]
[0056] The alloys can be formed into articles such as billets, plates, strips, foils, wires, rods, tubes, or bars. For purposes of this disclosure, a billet is a solid metal form, usually with a large cross-sectional area. A plate is a generally rectangular cross-section, flat surface product, having two straight sides, a uniform thickness greater than 4.8 millimeters (mm), a maximum thickness of about 210 mm, and a width greater than 30 mm. A strip is a generally rectangular cross-section, flat surface product, having two straight sides, a uniform thickness up to 4.8 millimeters (mm). This is typically done by rolling the charge to reduce its thickness to that of the strip. A bar is a generally rectangular cross-section, flat surface product, having a uniform thickness greater than 0.48 mm, and a maximum width of 30 mm. A wire is a solid cross-section other than strip, provided in a coil or on a spool or reel. A rod is a circular solid cross-section, provided in a straight length. A tube is a seamless hollow product, having a circular or other cross-section. Foils are very thin, flat surface products, typically with a uniform thickness of 0.04 mm or less. Note that these various articles may have some overlap.
[0052]
[0057] The copper alloys of the present disclosure can also be used to make specific articles of various shapes for various applications, such as heat sinks in cell phones, or a wide range of electrical and electronic devices, components, and parts, such as wires, cables, electrical connectors, electrical contacts, electrical ground plates, Faraday cage walls, heat spreaders, wire harness terminal contacts, processor socket contacts, backplanes, midplanes, or card edge server connectors, etc.
[0053]
[0058] The following examples are provided to illustrate the alloys, methods, articles, and properties of the present disclosure. The examples are merely exemplary and are not intended to limit the disclosure to the materials, conditions, or method parameters set forth above. EXAMPLES
[0054] Example 1
[0059] FIG. 2 is an image of an etched high conductivity Cu-Cr-Si-Ag-Ti-Zr alloy according to one embodiment of the present disclosure. The copper alloy shows improved precipitation strengthening. Zirconium oxide or chromium oxide lines are indicated by arrows and are benign. The circles indicate chromium silicide or chromium impurities. Zirconium silicide, which has the appearance of small needles and is detrimental to the strength of the alloy, was not observed. Without wishing to be bound by theory, it is believed that zirconium silicide typically forms at a temperature of about 1316° C. (about 2400° F.) and copper alloys never reach this temperature, therefore zirconium silicide never forms. Alternatively, zirconium is already bound to oxide or combined with chromium, so no free zirconium appears when zirconium silicide would normally precipitate.
[0055] Example 2
[0060] Several different alloys were made and processed according to the present disclosure. Their properties were then measured at several different times and averaged. Table A identifies the composition of the alloys for each heat in wt% (balance copper). Table B lists the processing parameters applied for each heat. "CW" is an abbreviation for cold work. The two solution annealing temperatures were both 988°C (1810°F). Table C provides all the measured results. Table D provides the average properties measured for each heat. GW and BW refer to formability measurements.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3-1]
[0059] [Table 3-2]
[0060] [Table 3-3]
[0061] [Table 4]
[0062] To summarize the results in Table D, the average 0.2% offset yield strength ranged from 75 ksi to 80 ksi. The average ultimate tensile strength (UTS) ranged from 80 ksi to 85 ksi. The average electrical conductivity (IACS%) ranged from 78 IACS% to 81 IACS%. The formability of all cooks was high.
[0063] Example 3
[0062] Several additional alloys were made and processed according to the present disclosure. Their properties were then measured at several different time points and averaged. Table E identifies the composition of the alloys for each heat in wt % (balance copper). All heats were solution annealed at temperatures between about 950°C (1742°F) and about 1050°C (1922°F), aged at 441°C (825°F) for 6 hours, and then aged at 427°C (800°F) for an additional 6 hours. Table F provides the average properties measured for each heat. GW and BW refer to formability measurements.
[0064] [Table 5]
[0065] [Table 6]
[0066] Comparative Example 1 A Cu-0.59Cr-0.16Ni-0.09Ag-0.04Si alloy was processed according to the present disclosure (i.e., three cold working steps, two solution annealing steps, and aging treatment). The resulting alloy had a 0.2% offset yield strength of 67.4 ksi and a conductivity of 78.5 IACS%.
[0067] Comparative Example 2 A Cu-0.94Cr-0.41Ni-0.15Si alloy was processed by three cold working steps and two solution annealing steps as described in this disclosure, and aged at 441° C. (825° F.) for three hours. The resulting alloy had a 0.2% offset yield strength of 73 ksi and a conductivity of 68 IACS%.
[0068] A variety of heat treatments were performed on this alloy. The measured 0.2% offset yield strengths ranged from 65 to 70 ksi, and the conductivity ranged from 62 to 67 IACS%.
[0069] For comparison, a Cu-Cr-Si-Ag-Ti-Zr alloy of the present disclosure was processed under the same parameters and had a 0.2% offset yield strength of 74 ksi and a conductivity of 74 IACS%, i.e., higher values for both properties.
[0070] Comparative Example 3
[0067] Several Ni-Cr-Si-Mn-Zr alloys were prepared and processed similarly to the present disclosure. Instead of three cold work steps and two solution annealing steps before aging as in the present disclosure, these alloys were processed with two cold work steps and one solution annealing step before aging.
[0071] The properties were then measured and averaged. Table E identifies the alloy composition for each heat in wt % (balance copper). Table F lists the processing parameters applied to each heat. "CW" is an abbreviation for cold work. The two solution annealing temperatures were both 988°C (1810°F). Table G provides the average properties measured for each run.
[0072] [Table 7]
[0073] [Table 8]
[0074] [Table 9]
[0075]
[0069] As can be seen, the IACS% for these alloys is relatively low, not exceeding 53 IACS%.
[0070] The present disclosure has been described with reference to exemplary embodiments. Modifications and alterations will occur to those skilled in the art upon reading and understanding the foregoing detailed description. It is intended that the present disclosure be construed as including all such modifications and alterations insofar as they come within the scope of the appended claims or the equivalents thereof. Specific embodiments of the present invention are as follows. [Aspect 1] A copper alloy, Approximately 0.5wt% to 1wt% chromium, about 0.02 wt% to about 0.1 wt% silicon, Approximately 0.1wt% to 0.2wt% silver, Approximately 0.015wt% to approximately 0.05wt% titanium, about 0.02 wt% to about 0.06 wt% zirconium, and Residual copper Including, having a 0.2% offset yield strength of at least 70 ksi and an electrical conductivity of at least 75% IACS; The copper alloy. [Aspect 2] 2. The copper alloy of embodiment 1, further having an ultimate tensile strength of at least 80 ksi. [Aspect 3] The copper alloy of embodiment 1 or 2, further having a total elongation to break % of at least 7%. [Aspect 4] 4. The copper alloy of any of the preceding embodiments, further having a formability ratio of 0.0 / 0.0. [Aspect 5] 5. The copper alloy of any of the preceding embodiments, having a 0.2% offset yield strength of at least 75 ksi and an electrical conductivity of at least 80% IACS. [Aspect 6] 2. The copper alloy of embodiment 1, having a 0.2% offset yield strength of at least 70 ksi, an electrical conductivity of at least 75% IACS, an ultimate tensile strength of at least 75 ksi, and a % total elongation to break of at least 7%. [Aspect 7] 7. The copper alloy of any of the preceding embodiments, wherein the copper alloy does not contain tin or beryllium. [Aspect 8] 8. The copper alloy according to any one of the preceding aspects, which is free of zirconium silicide. [Aspect 9] 9. An article formed from the copper alloy of any of claims 1 to 8. [Aspect 10] The article of embodiment 9, wherein the article is a billet, plate, strip, foil, wire, rod, tube, or bar. [Aspect 11] 1. A method of making a copper alloy, comprising the steps of: cold working the copper alloy to a first cold work percentage (CW%); solution annealing the cold worked copper alloy a first time for a first period of time; cold working the annealed copper alloy to a second CW%; solution annealing the cold worked copper alloy a second time for a second period of time; cold working the solution annealed copper alloy to a third CW%; and Aging the cold worked copper alloy for a third period of time to obtain said copper alloy. Including, The copper alloy has a yield strength of at least 70 ksi and a conductivity of at least 75% IACS. The method. [Aspect 12] The method of embodiment 11, wherein the first CW% is about 60% to about 95%. [Aspect 13] 13. The method of any one of aspects 11 or 12, wherein the second CW% is about 30% to about 80%. [Aspect 14] 14. The method according to any one of aspects 11 to 13, wherein the third CW% is about 30% to about 80%. [Aspect 15] 15. The method of any one of aspects 11 to 14, wherein the minimum cumulative cold work is at least 85%. [Aspect 16] 16. The method of any one of aspects 11 to 15, wherein the first solution annealing is carried out at a temperature of about 950°C to about 1050°C. [Aspect 17] 17. The method according to any one of aspects 11 to 16, wherein the first period of time is from about 1 minute to about 10 minutes. [Aspect 18] 18. The method of any one of aspects 11 to 17, wherein the second solution annealing is carried out at a temperature of about 950° C. to about 1050° C. [Aspect 19] 19. The method according to any one of aspects 11 to 18, wherein the second period of time is from about 1 minute to about 10 minutes. [Aspect 20] 20. The method according to any one of aspects 11 to 19, wherein the aging treatment is carried out at a temperature of about 400°C to about 500°C. [Aspect 21] 21. The method according to any one of aspects 11 to 20, wherein the third period of time is from about 4 hours to about 20 hours. [Aspect 22] 22. The method of any one of aspects 11 to 21, wherein the aging treatment is carried out in a full hydrogen atmosphere. [Aspect 23] The copper alloy is Approximately 0.5wt% to 1wt% chromium, about 0.02 wt% to about 0.1 wt% silicon, Approximately 0.1wt% to 0.2wt% silver, Approximately 0.015wt% to approximately 0.05wt% titanium, about 0.02 wt% to about 0.06 wt% zirconium, and Residual copper 23. The method of any of embodiments 11 to 22, comprising: [Aspect 24] 24. A copper alloy produced by the method of any one of embodiments 11 to 23.
Claims
1. An article, comprising: 0.5 wt % to 1 wt % chromium, 0.02 wt % to 0.1 wt % silicon, 0.1 wt % to 0.2 wt % silver, 0.015 wt % to 0.05 wt % titanium; 0.02 wt % to 0.06 wt % zirconium, unavoidable impurities, and Residual copper It consists of: having a 0.2% offset yield strength of at least 70 ksi and an electrical conductivity of at least 75% IACS; The above-mentioned item.
2. The article of claim 1 further having an ultimate tensile strength of at least 80 ksi.
3. 3. The article of claim 1 or 2, further having a total elongation at break percentage of at least 7%.
4. 4. The article of any one of claims 1 to 3, further comprising a formability ratio of 0.0 / 0.0, where the formability ratio is expressed as GW / BW, where GW is the machine direction formability (R / t) and BW is the cross direction formability (R / t) when a minimum inside radius of curvature (R) required to bend a strip of thickness (t) 90 degrees without failure is specified.
5. 5. The article of any of claims 1 to 4, having a 0.2% offset yield strength of at least 75 ksi and an electrical conductivity of at least 80% IACS.
6. 10. The article of claim 1 having a 0.2% offset yield strength of at least 70 ksi, an electrical conductivity of at least 75% IACS, an ultimate tensile strength of at least 75 ksi, and a total elongation to break % of at least 7%.
7. 7. The article of any one of claims 1 to 6, which does not contain tin or beryllium.
8. 8. The article of any one of claims 1 to 7, which is free of zirconium silicide.
9. 10. The article of claim 1 which is a plate, strip, foil, wire, rod, tube, or bar.
10. 1. A method of making a copper alloy, comprising the steps of: cold working the copper alloy to a first cold work percentage (CW%); solution annealing the cold worked copper alloy a first time for a first period of time; cold working the annealed copper alloy to a second CW %; solution annealing the cold worked copper alloy a second time for a second period of time; cold working the solution annealed copper alloy to a third CW %; and Aging the cold worked copper alloy for a third period of time to obtain said copper alloy. Including, The copper alloy obtained after the aging treatment has a yield strength of at least 70 ksi and a conductivity of at least 75% IACS, 0.5 wt % to 1 wt % chromium, 0.02 wt % to 0.1 wt % silicon, 0.1 wt % to 0.2 wt % silver, 0.015 wt % to 0.05 wt % titanium; 0.02 wt % to 0.06 wt % zirconium, unavoidable impurities, and Residual copper The method comprising:
11. The method of claim 10, wherein the first CW% is between 60% and 95%.
12. The method of claim 10 or 11, wherein the second CW% is between 30% and 80%.
13. The method according to any one of claims 10 to 12, wherein the third CW% is between 30% and 80%.
14. 14. The method of any of claims 10 to 13, wherein the minimum cumulative cold work is at least 85%.
15. The method according to any of claims 10 to 14, wherein the first solution annealing is carried out at a temperature between 950°C and 1050°C.
16. The method of any of claims 10 to 15, wherein the first period of time is between 1 minute and 10 minutes.
17. The method according to any of claims 10 to 16, wherein the second solution annealing is carried out at a temperature between 950°C and 1050°C.
18. The method of any of claims 10 to 17, wherein the second period of time is between 1 minute and 10 minutes.
19. The method according to any of claims 10 to 18, wherein the ageing treatment is carried out at a temperature between 400°C and 500°C.
20. 20. The method of any of claims 10 to 19, wherein the third period of time is from 4 hours to 20 hours.
21. 21. The method according to any of claims 10 to 20, wherein the ageing treatment is carried out in a full hydrogen atmosphere.
Citation Information
Patent Citations
Silver containing copper alloy
JP2008057046A
Age-hardening copper-base alloy and processing
JP2010275640A
Method of manufacturing copper alloy for electronic material
JP2012012630A
Copper alloy sheet having excellent strength and conductivity
JP2018159104A